Enhanced photocatalytic hydrogen evolution of CdWO4 through polar organic molecule modification. (22nd February 2019) - Xing, Danning; Liu, Yuanyuan; Zhou, Peng; Wang, Zeyan; Wang, Peng; Zheng, Zhaoke; Zhang, Xiaoyang; Qin, Xiaoyan; Dai, Ying; Huang, Baibiao
Abstract: In this work, a polar molecule 4-mercaptobenzoic acid (4-MBA) is anchored on the surface of CdWO4 by forming CdS and WS bond. Photocatalytic hydrogen evolution is significantly enhanced (about 3.41 times) after the modification. The reason is due to the modification of 4-MBA, which results in a polar surface and built-in electric field. The polar surface is confirmed byt he steady state and time-resolved PL spectra, Voc and SHG results. Graphical abstract: Image 1 Highlights: A polar molecule is anchored on the surface of CdWO4 by forming CdS and WS bond, resulting in built-in electric field. 4-MBA modification leads to improved photocatalytic activity not only towards RhB degradation, but also H2 evolution. Photocatalytic hydrogen evolution performance of CdWO4 is significantly enhanced after the modification, about 3.41 times. Polar molecular modification is beneficial to the photogenerated charge separation.